A Drinking Problem: French Psychiatric Fears about the Increase in Muslim Alcoholics in Colonial Algeria - Nina Salouâ Studer (Revue des Mondes Musulmans et de la Méditerranée)
Until the establishment of psychiatric institutions in the colonial Maghreb in the 1930s, the consensus of most colonial French psychiatrists was that alcoholism had previously been unknown amongst Muslim North Africans, but that it was quickly becoming a medical, social and economic problem. They voiced fears of an explosion in numbers of psychiatric patients due to this increase in alcoholism and a corresponding increase in crimes committed by intoxicated Muslim men. These psychiatrists also described alcoholism as a serious problem among male and female French settlers in Algeria, while suggesting that most Muslim women did not consume any alcohol, even though they regularly commented on the excessive alcohol consumption of certain marginalised Muslim women they encountered. These accounts strongly pathologised and criminalised alcohol-drinking Muslims, framing them as being just one glass away from ending up in a prison or psychiatric hospital.